2016
DOI: 10.3390/jcm5090078
|View full text |Cite
|
Sign up to set email alerts
|

Real World Experiences: Pirfenidone and Nintedanib are Effective and Well Tolerated Treatments for Idiopathic Pulmonary Fibrosis

Abstract: Idiopathic Pulmonary Fibrosis (IPF) now has two licensed treatments available. Pirfenidone was the first drug to be licensed and approved for use, followed by nintedanib. We set out our real world experience with these agents in terms of their adverse events profile outside the restrictions of a clinical trial. We have demonstrated in the real world setting, that side effects are common and predominantly gastrointestinal with both therapies. Our study shows that the side effects can be effectively managed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
109
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(128 citation statements)
references
References 16 publications
(38 reference statements)
15
109
4
Order By: Relevance
“…The demographic characteristics of the patients reported in this study, including age, sex distribution, and smoking history, were broadly similar to those reported in the previous INPULSIS trials [11] as well as to those reported in other real-world reports [15, 16], reflecting the typical patient demographic characteristics of patients with IPF. Subgroup analyses of the INPULSIS trials have shown that the treatment effects of nintedanib are consistent across patient subgroups, including sex, age, smoking status, and baseline respiratory functions measured using baseline percent predicted FVC [26].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The demographic characteristics of the patients reported in this study, including age, sex distribution, and smoking history, were broadly similar to those reported in the previous INPULSIS trials [11] as well as to those reported in other real-world reports [15, 16], reflecting the typical patient demographic characteristics of patients with IPF. Subgroup analyses of the INPULSIS trials have shown that the treatment effects of nintedanib are consistent across patient subgroups, including sex, age, smoking status, and baseline respiratory functions measured using baseline percent predicted FVC [26].…”
Section: Discussionsupporting
confidence: 74%
“…As such, our data provide support for the benefits of nintedanib in a patient population with more severe disease at baseline; nintedanib treatment was associated with stable disease at 6 months, as measured by FVC, in the majority (67%) of patients. The baseline respiratory function reported in our real-world cohort was similar to that in patients treated in other real-world analyses [15, 16]. …”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In a single-centre, retrospective, observational study of 351 patients who were receiving pirfenidone, 75% of reported AEs were GI-related, with loss of appetite (17%) and nausea/vomiting (15%) being most frequent, similar to what was observed in the phase III trials [10,11,33]. The highest number of treatment discontinuations occurred with appetite loss and nausea/vomiting (28 and 22, respectively).…”
Section: Dose Modificationsmentioning
confidence: 70%
“…Nintedanib is therefore contra-indicated in patients with significant active cardiovascular disease and those taking dual anti-platelet therapy or warfarin. Post-trial and realworld data has not demonstrated any additional safety signals with respect to cardiovascular and bleeding risks (16,21). Nintedanib is contraindicated in patients with peanut allergy.…”
Section: Adverse Effects Of Antifibroticmentioning
confidence: 99%